2018
DOI: 10.1103/physrevd.98.015025
|View full text |Cite
|
Sign up to set email alerts
|

Matter density profile shape effects at DUNE

Abstract: Quantum mechanical interactions between neutrinos and matter along the path of propagation, the Wolfenstein matter effect, are of particular importance for the upcoming long-baseline neutrino oscillation experiments, specifically the Deep Underground Neutrino Experiment (DUNE). Here, we explore specifically what about the matter density profile can be measured by DUNE, considering both the shape and normalization of the profile between the neutrinos' origin and detection. Additionally, we explore the capabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…We focus on the Deep Underground Neutrino Experiment (DUNE) [43] experimental conditions 2 of L = 1300 km and Earth density of ρ = 3 g/cm 3 . We take the matter density to be constant, which is a good approximation since effects due to the variability of the density of the Earth are beyond the sensitivity of DUNE [44]. The results will also generally apply to other long-baseline experiments such as NOVA [45], T2K/HK [46,47].…”
Section: Neutrino Oscillations In Constant Mattermentioning
confidence: 99%
“…We focus on the Deep Underground Neutrino Experiment (DUNE) [43] experimental conditions 2 of L = 1300 km and Earth density of ρ = 3 g/cm 3 . We take the matter density to be constant, which is a good approximation since effects due to the variability of the density of the Earth are beyond the sensitivity of DUNE [44]. The results will also generally apply to other long-baseline experiments such as NOVA [45], T2K/HK [46,47].…”
Section: Neutrino Oscillations In Constant Mattermentioning
confidence: 99%
“…• A "naive" estimate based on the method described in [11]. This is used as a cross-check, as comparisons between both methods allow us to be confident about the shapes produced.…”
Section: Sensitivity Estimatesmentioning
confidence: 99%
“…For DUNE it has been shown that varying the density profile would have no measurable effect on oscillations [11], and studies of previous designs for longbaseline experiments with beams originating in Japan found similarly small effects [12][13][14][15][16]. This study aims to determine whether the geographical features present in the baselines for the approved T2HK and proposed T2HKK projects could produce a different conclusion.…”
Section: Introductionmentioning
confidence: 97%
“…The effects of matter density variation and its average along the beam path from Fermilab to SURF were studied considering the standard neutrino oscillation framework with three flavors [399,400].…”
Section: Effects Of Baseline and Matter-density Variation On Nsi Measmentioning
confidence: 99%
“…However, a more detailed density map is available for the USA with more than 50 layers and 0.25 × 0.25 degree cells of latitude and longitude: The Shen-Ritzwoller or S.R. profile [403, [400] show that, in the standard oscillation paradigm, DUNE is not highly sensitive to the density profile and that the only oscillation parameter with its measurement slightly impacted by the average density true value is δ CP . NSI, however, may be sensitive to the profile, particularly considering the phase φ eτ [404], to which DUNE will have a high sensitivity [390,391,388,389,316], as we also see in Figure 8.7.…”
Section: Effects Of Baseline and Matter-density Variation On Nsi Measmentioning
confidence: 99%